Territorial Marketing: A useful tool for competitiveness of rural and peripheral areas - Anabela Dinis (European Regional Science Association (ERSA), 2004)
Over recent years territorial cohesion has become an important concern for national and supra-national governments. This concern stems from the unexpected growth in spatial imbalance in terms of economic development. Urban and more developed areas are attracting more and more people and economic activities, while a great part of rural and peripheral territories seem condemned to desertification and abandonment. This is clearly the case of Portugal. This paper shows how the application of marketing tools and philosophy can be used to reverse (or at least slow down) this process when applied to the formulation and implementation of territorial development strategies. With this in mind, the issue of territorial development is looked at and marketing concepts are introduced. Considering rural and peripheral territories as the product to be marketed, the main components of its marketing system are discussed and some of the current trends in society that affect supply and demand of the rural product are presented. Under the light of this theoretical framework, some guidelines for action and the main responsible agents are identified in order to improve the competitiveness of rural and peripheral areas Key words: Rural and peripheral territories, Marketing, Competitiveness
Keywords: 330; Rural and peripheral territories; Marketing; Competitiveness